The Role of Inflammatory Biomarkers RBP4, Lipocalin-2, and hsCRP in Prediabetes and Type 2 Diabetes Mellitus: Inflammatory Biomarkers in Prediabetes - oğuz, OSMAN; Örnek Diker, Vesile; serin, Özden; Yorulmaz Ertuğ, Ebru; Baytekin, Özlem; Güvenen, Güvenç (Journal of Medical Biochemistry, 2025)
Background: Adipocytokines, along with macrophages infiltrating adipose tissue, contribute to chronic low-grade inflammation, which leads to insulin resistance and type 2 diabetes. Understanding insulin resistance in non-diabetic individuals and its cellular mechanisms is key for developing effective treatments and improving current protocols. This study aimed to investigate the levels of Retinol Binding Protein 4 (RBP4), Lipocalin-2, and high-sensitivity C-reactive protein (hsCRP) in individuals with impaired fasting glucose (IFG), impaired glucose tolerance (IGT), and type 2 diabetes mellitus (T2DM). Methods: This prospective case-control study study included individuals with IFG, IGT, and newly diagnosed T2DM. Routine laboratory tests, including fasting blood glucose, insulin, HbA1c, and lipid profiles, were collected and analyzed. RBP4, Lipocalin-2, and hsCRP levels were measured using the ELISA method. Results: Significant differences were found in fasting blood glucose, insulin, triglycerides, total cholesterol, and HOMA-IR values among the study groups. hsCRP levels were significantly elevated in the IGT and T2DM groups compared to controls, while RBP4 and Lipocalin-2 levels showed no significant differences. A positive correlation was observed between hsCRP and HbA1c in the IFG group, as well as between hsCRP and Lipocalin-2 in the T2DM group. Conclusion: This study demonstrates that hsCRP and Lipocalin-2 are associated with early glucose metabolism abnormalities and may serve as markers for insulin resistance and inflammation in prediabetes and T2DM. Future research is needed to clarify the roles of these biomarkers and their potential as therapeutic targets in diabetes prevention and treatment